CASE REPORT: BILATERAL OTITIS EXTERNA DUE TO PROTEUS SPP. INFECTION IN A PERSIAN CAT - Kadek Mahardika; I Putu Gede Yudhi Arjentinia; Sri Kayati Widyastuti (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
External otitis is a commonly encountered ear disease in cats, characterized by inflammation of the external auditory canal and influenced by predisposing, primary, secondary, and perpetuating factors. This case report describes a six-year-old male Persian cat with a history of recurrent external otitis. The cat was presented to the Internal Medicine Laboratory, Faculty of Veterinary Medicine, Udayana University, Denpasar, Bali, with primary complaints of frequent ear scratching, head shaking, and the presence of yellow, foul-smelling discharge from both ears. Physical examination revealed yellowish, watery cerumen with a strong odor. Cytological examination demonstrated abundant rod-shaped bacteria, and bacterial culture confirmed the growth of Proteus spp. A diagnosis of bilateral external otitis caused by Proteus spp. infection was established, with a favorable prognosis. The treatment consisted of topical administration of Topigen® ear drops containing gentamicin sulphate (1.6 mg/mL), nystatin (100,000 IU/mL), and fluocinolone acetonide (0.25 mg/mL), administered at a dosage of three drops twice daily for 12 days, accompanied by routine ear cleaning using an otic cleansing solution. Clinical evaluation after 12 days of treatment showed significant improvement, characterized by reduced cerumen production, resolution of malodor, and the absence of inflammatory signs on otoscopic examination. This report underscores the importance of cytological examination and bacterial culture in establishing an accurate diagnosis and demonstrates the effectiveness of combination topical antibiotic and anti-inflammatory therapy in the management of bacterial external otitis.